Nitrogen and Oxygen Regulation of Bacillus subtilis nasDEF Encoding NADH-Dependent Nitrite Reductase by TnrA and ResDE - Nakano, Michiko M. (American Society for Microbiology, 1998)
The nitrate and nitrite reductases of Bacillus subtilis have two different physiological functions. Under conditions of nitrogen limitation, these enzymes catalyze the reduction of nitrate via nitrite to ammonia for the anabolic incorporation of nitrogen into biomolecules. They also function catabolically in anaerobic respiration, which involves the use of nitrate and nitrite as terminal electron acceptors. Two distinct nitrate reductases, encoded by narGHI and nasBC, function in anabolic and catabolic nitrogen metabolism, respectively. However, as reported herein, a single NADH-dependent, soluble nitrite reductase encoded by the nasDE genes is required for both catabolic and anabolic processes. The nasDE genes, together with nasBC (encoding assimilatory nitrate reductase) and nasF (required for nitrite reductase siroheme cofactor formation), constitute the nas operon. Data presented show that transcription of nasDEF is driven not only by the previously characterized nas operon promoter but also from an internal promoter residing between the nasC and nasD genes. Transcription from both promoters is activated by nitrogen limitation during aerobic growth by the nitrogen regulator, TnrA. However, under conditions of oxygen limitation, nasDEF expression and nitrite reductase activity were significantly induced. Anaerobic induction of nasDEF required the ResDE two-component regulatory system and the presence of nitrite, indicating partial coregulation of NasDEF with the respiratory nitrate reductase NarGHI during nitrate respiration.